Improving middle school students’ mathematical literacy through problem-based learning: Considering early mathematical abilities - Hasanah, Aan; Marasabessy, Rosida; Samsudin, Samsudin (Indonesian Journal of Science and Mathematics Education, 2026)
Mathematical literacy is an essential 21st-century competency; however, PISA reports indicate that Indonesian middle school students’ performance remains low. This gap highlights the urgency of implementing instructional strategies that promote meaningful contextual problem-solving. This study aims to examine the effect of Problem-Based Learning (PBL) on students’ improvement in mathematical literacy in statistics, while accounting for their early mathematical abilities (EMA). This study used a quasi-experimental, non-equivalent control group design involving 64 seventh-grade students from a junior high school in Bandung. Data were collected through pretest and posttest and analyzed using N-gain scores, a one-tailed independent t-test, and One-Way ANOVA. The results revealed that the mean N-gain of the PBL group was 0.4752 (moderate), higher than that of the direct instruction group at 0.2157 (low). The difference was statistically significant (Sig. = 0.000 < 0.05). Based on EMA levels, the mean N-gain scores were 0.7989 (high) for high EMA, 0.4077 (moderate) for medium EMA, and 0.4486 (moderate) for low EMA students. ANOVA results indicated significant differences among EMA categories (Sig. = 0.000 < 0.05). This finding suggests that PBL influences improvements in mathematical literacy and accounts for students' initial abilities.